Aproximación a la fundamentación de las culturas del Perú antiguo como estados - Espinoza Coila, Michael (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2023)
This chapter of the book exposes the results of a brief investigation of grounded theory design that responds to the statement: Are the cultures of ancient Peru States? To answer this question, the objective of establishing the status of State of the cultures of the Ancient Peru, because they comply with the elements and other aspects of the Theory of the State. The results contribute to the Theory of the Peruvian State as part of the current emancipatory process ofautochthonous knowledge that values the materiality and spirituality of the settler of ancient Peru.